Analysis of seasonal biomass variation of the three main seagrass species in the Venice Lagoon along different environmental gradients in urban and natural sites - LIONELLO, JACOPO (2024)
reserved Seagrasses are a small group of marine angiosperms that colonize the majority of coastal and estuarine habitats worldwide, from the tropics to subarctic regions. These plants are fully adapted to live submerged in shallow waters, provide crucial ecosystem services, such as carbon sequestration, primary and oxygen production, and act as nursery for fish of commercial importance. However, since the past century, seagrass meadows have dramatically declined in density, even disappearing entirely from many coastal regions around the world due to significant human impact, and unfortunately, this trend continues today. Since the late 20th century the importance of seagrasses has become widely recognized, leading to numerous efforts to protect the remaining seagrass meadows and restore those lost, such as in the Venice Lagoon. Since then, many studies have focused on seagrass physiology, behaviour, and restoration, crucial to ongoing conservation efforts. For this reason, this study aims to understand how the three main seagrasses of the Venice Lagoon - Zostera marina, Zostera noltii and Cymodocea nodosa - behave in different levels of stress in terms of biomass and primary production, starting from natural (low level of stress), periurban (intermediate level of stress) and urban environments (high level of stress). Also, the seasonal influences over the seagrass biomass will be caried out, giving importance also to the mutual interactions between the three species, to include all possible reason in biomass variations in their habitats. The biomass data for the three species reveal clear correlations with the environmental gradient they live in. Z. noltii and Z. marina are the most sensitive to stressful conditions, showing reduced biomasses for both AG (above ground) and BG (below ground) in urban sites. In contrast, C. nodosa exhibits the opposite trend, achieving its highest AG and BG biomasses in urban areas. The results also highlight seasonal biomass patterns and demonstrate how changes in water ...